(untitled) (Eurasian Scientific Herald, 2023)
This article is written to show that there are a lot of different ways of teaching foreign languages young learners at the beginning stage. This article consists of different tips, which can help teachers to work with children and adults. Psychological peculiarities of children and adults are describing in this work.